The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/cgf.13188
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Personal Image Collections with PICTuReVis

Abstract: Digital image collections contain a wealth of information, which for instance can be used to trace illegal activities and investigate criminal networks. We present a method that enables analysts to reveal relations among people, based on the patterns in their collections. Similar temporal and spatial patterns can be found using a parameterized algorithm, visualization is used to choose the right parameters and to inspect the patterns found. The visualization shows relations between image properties: the person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Where this article focuses on the effect of the shuffled ImageNet bank for event detection and search, the concept bank is of interest in more research problems. The previous iteration of the bank [40] has already found applications in video captioning [11], visualizing image collections [61], and detecting violence in videos [32] amongst others. We hope that by making the shuffled ImageNet banks of this article publicly available, a broad range of multimedia problems can benefit from the concept bank representations.…”
Section: Discussionmentioning
confidence: 99%
“…Where this article focuses on the effect of the shuffled ImageNet bank for event detection and search, the concept bank is of interest in more research problems. The previous iteration of the bank [40] has already found applications in video captioning [11], visualizing image collections [61], and detecting violence in videos [32] amongst others. We hope that by making the shuffled ImageNet banks of this article publicly available, a broad range of multimedia problems can benefit from the concept bank representations.…”
Section: Discussionmentioning
confidence: 99%
“… 2010 ) arranged all images and associate metadata in a tabular layout. PICTuReVis (van der Corput and van Wijk 2017 ) showed that relations among people can be revealed based on image collections. StreetVizor (Shen et al.…”
Section: Related Workmentioning
confidence: 99%
“…Serving as the epicenter of research on interactive multimedia retrieval, the initiatives such as Video Browser Showdown produced a number of excellent analytics systems [13]. [24] GraphViz [9] PIWI [35] Newdle [36] Gephi [2] CoMeRDA [5] Blackthorn [38] vitrivr [20] SIRET [12] Vibro [1] PICTuReVis [29] ISOLDE For example, vitrivr system owes it good performance in interactive multimedia retrieval to an indexing structure for efficient kNN search [20]. Similarly, SIRET tool facilitates interactive video retrieval using several querying strategies, i.e.…”
Section: Multimedia Analyticsmentioning
confidence: 99%
“…Finally, while PICTuReVis [29] facilitates interactive learning for revealing relations between users based on their patterns of multimedia consumption, it is not designed for search and exploration of large social multimedia networks, but rather forensic analysis of artifacts from e.g. confiscated electronic devices, featuring a limited number of users.…”
Section: Multimedia Analyticsmentioning
confidence: 99%